Statecraft and security the Cold War and beyond - Booth, Ken 1943- (Cambridge University Press, 1998)
In this book a group of influential and distinguished scholars analyse some of the key questions in contemporary international relations. The book is in three parts. In the first, the lessons and legacies of Cold War are examined, including debates about its rise and fall, and the implications of the superpower nuclear confrontation. Part II asks questions about powers and politics in the post-Cold War world: the USA's potential as a world leader, Russia's troubled future, Japan's potential power, the China syndrome, and Africa's problems. The final part looks further into the future, discussing international organisation, life politics, and the potentialities for human society under the conditions of globalisation. The book shows how different countries and different groups of countries are confronting urgent issues of statecraft in a period of radical global transformation
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1989-1998; World politics / 1989-; Cold War / Influence; Ost-West-Konflikt; Internationale Politik; Aufsatzsammlung